Preventive Measures for Juvenile Crimes in Yogyakarta City - Isnawan, Fuadi (KnE Social Sciences, 2023)
This study examined how to effectively and efficiently deal with juvenile delinquency through klithih. This research was conducted normatively, and the results showed that several measures must be undertaken to handle juvenile delinquency, including the use of criminal law in a way that does not involve criminal sanctions but by using the mass media instead to punish the juveniles who commit the illegal actions in a way that it would implant fear when they intend to perform the crime. The conclusion was that there are various ways to overcome juvenile delinquency, among others, by strengthening the mentality of adolescents, and understanding adolescents and those who are approaching them so that they can minimize the difficulties that would otherwise be their means to vent the inability to commit juvenile delinquency Keywords: Adolescence, Juvenile Crimes, Preventive